2012
DOI: 10.3168/jds.2011-4998
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with frequency of abortions recorded through Dairy Herd Improvement test plans

Abstract: Frequency of abortions recorded through Dairy Herd Improvement (DHI) testing was summarized for cows with lactations completed from 2001 through 2009. For 8.5 million DHI lactations of cows that had recorded breeding dates and were >151 d pregnant at lactation termination, the frequency of recorded abortions was 1.31%. Effects of year, herd-year, month, and pregnancy stage at lactation termination; parity; breed; milk yield; herd size; geographic region; and state within region associated with DHI-recorded abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 27 publications
6
25
2
4
Order By: Relevance
“…The economic loss from a midterm abortion is estimated to be about $800 (Norman et al, 2012), for a total cost of ~$420 million. For comparison, the increased value of milk from using Chief instead of an average bull in 1962 is his genetic contribution to the breed (0.143) × the farm price of milk ($0.33/L) × the increased milk yield (2 L/d) × 305 d/yr × 35 yr × 30 million cows = $30 billion.…”
Section: Calculations Supporting Chief's Influence On Spontaneous Abomentioning
confidence: 99%
See 1 more Smart Citation
“…The economic loss from a midterm abortion is estimated to be about $800 (Norman et al, 2012), for a total cost of ~$420 million. For comparison, the increased value of milk from using Chief instead of an average bull in 1962 is his genetic contribution to the breed (0.143) × the farm price of milk ($0.33/L) × the increased milk yield (2 L/d) × 305 d/yr × 35 yr × 30 million cows = $30 billion.…”
Section: Calculations Supporting Chief's Influence On Spontaneous Abomentioning
confidence: 99%
“…For comparison, the increased value of milk from using Chief instead of an average bull in 1962 is his genetic contribution to the breed (0.143) × the farm price of milk ($0.33/L) × the increased milk yield (2 L/d) × 305 d/yr × 35 yr × 30 million cows = $30 billion. Embryonic and fetal loss during gestation was investigated using the national fertility database and occurred mainly from 60 to 200 d of gestation for HH1, but earlier for several other recessive defects (VanRaden et al, 2011a; see also Norman et al, 2012 for more details on the timing of embryo loss, and Fritz et al, 2013 for independent confirmation of fertility effects).…”
Section: Calculations Supporting Chief's Influence On Spontaneous Abomentioning
confidence: 99%
“…The decrease in milk yield is partly due to endocrine changes, not just the immediate effects of having less available energy when DMI decreases (Rhoads et al, 2010). In many cases, cows do not return to their level of milk yield before the heat stress event, and under severe heat stress, cows may abort a pregnancy or even die (Stull et al, 2008;Norman et al, 2012). Climate change could exacerbate these losses by making the climate warmer or more variable (Crescio et al, 2010).…”
Section: Introductionmentioning
confidence: 95%
“…Finally, cattle owners are traditionally of the opinion that they only have to notify abortion in case of observation of the expulsion of a dead or non-viable foetus during mid-and end-gestation. Therefore, taking all these factors into consideration, the authors postulated that the percentage of cattle with a notified abortion is not likely to be higher than 1% in Belgium, which is in line with the study of Norman et al (2012) who found an abortion frequency of 1.31% in dairy cattle over 151 days of pregnancy.…”
Section: Calculation Of the Animal Health Barometermentioning
confidence: 55%